PERANAN DOA SYAFAAT DALAM MEWUJUDKAN KESETIAAN MELAYANI PARA PENGERJA DI GEREJA BETHEL INDONESIA GEDUNG TABGHA BATAM CENTER - Tony Suhartono; Irma Ompusunggu (JURNAL TABGHA, 2023)
Prayer is a very essential need in the spiritual life of believers, prayer is a spiritual breath to revive the human spirit, Prayer is believed to be one of the means to communicate to the God who is worshipped, through intercession the believer is connected to the source of life, namely God himself. In the human body, the organ that continues to work and never stops is the heart, anyone knows that. If the heart stops all the organs in the body of a believer can also stop, so does prayer, if prayer stops the spiritual life of a believer can also stop.Intercessory prayer speaks that humans need each other, intercessory prayer in which believers, mediating between sinful humans and God, speak of a very close relationship with faithfulness. God created humans as social beings, in carrying out life, they definitely need other humans as well as intercessory prayers that need each other, where they pray for each other for the safety of mankind. Likewise, loyalty starts from a close relationship that requires each other so that the relationship becomes strong. Loyalty is something that is very expensive and very rare in this day and age, intercessory prayer is a means of building a relationship with God, so loyalty will be built day by day.The purpose of the role of intercessory prayer is so that church servants really understand and understand about intercessory prayer in realizing faithfulness to serve.